2018
DOI: 10.1016/j.bbmt.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Transplant Outcomes for Secondary Acute Myeloid Leukemia: Acute Leukemia Working Party of the European Society for Blood and Bone Marrow Transplantation Study

Abstract: Secondary acute myeloid leukemia (sAML) has been associated with inferior outcomes compared with de novo AML. Little is known about patient risk factors and outcomes in sAML after allogeneic hematopoietic stem cell transplantation (HCT); thus, this large systemic analysis of the European Society for Blood and Bone Marrow Transplantation registry was performed. This study included 4997 patients with sAML who received HCT from 2000 to 2016. In univariate analysis the 2-year cumulative incidence of chronic graft-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 36 publications
12
44
2
Order By: Relevance
“…Although there are no pathognomonic genetic aberrations known for tAML, this subgroup had a worse outcome than MDS-related AML in several studies 2,7,14,24 . In a previous study from our group, slight differences in NRM and survival had been observed between patients with AML evolving from MDS/MPN and other hematologic malignancies, but not solid tumors 8 . In the present analysis, we therefore repeated the Cox model including tAML and AML evolving from another hematologic disease, as covariates.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although there are no pathognomonic genetic aberrations known for tAML, this subgroup had a worse outcome than MDS-related AML in several studies 2,7,14,24 . In a previous study from our group, slight differences in NRM and survival had been observed between patients with AML evolving from MDS/MPN and other hematologic malignancies, but not solid tumors 8 . In the present analysis, we therefore repeated the Cox model including tAML and AML evolving from another hematologic disease, as covariates.…”
Section: Discussionmentioning
confidence: 57%
“…Secondary AML was defined as AML with an antecedent MDS, MPN or other malignant hematologic disorder, bone marrow failure syndrome, or solid tumor with prior chemotherapy or radiation 8 . For a subgroup analysis, tAML was defined by previous treatment of solid tumors, Hodgkin or non-Hodgkin Lymphoma (NHL), acute lymphoblastic leukemia (ALL) or chronic lymphocytic leukemia (CLL) using chemotherapy or radiation 14 .…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported outcomes for 3,960 patients with sAML who underwent allogeneic HSCT during the years of 2000‒2016 (of whom 41% had active disease not in remission). Two‐year leukaemia‐free survival (see Figure , from Sengsayadeth et al , ), overall survival, and non‐relapse mortality were 39%, 45% and 28%, respectively. In comparison, the subgroup of patients with sAML who had been transplanted and with active disease, had two‐year leukaemia‐free survival, overall survival, and non‐relapse mortality rates of 29%, 35% and 33%, respectively.…”
Section: Current Standard For Treatment Of Samlmentioning
confidence: 95%
“…This procedure provided a 2-year OS rate of 52.3% (95% CI, 50. 2-54.4) in a recent large retrospective study assessing allo-HSCT from various sources in patients with sAML in CR1 [12]. Further, allo-HSCT has been considered as the only curative treatment for patients with refractory or relapsing sAML, providing 2-year OS rates of 34.5% (95% CI, 32.3-36.7) in the same large retrospective study [12].…”
Section: Introductionmentioning
confidence: 99%